98% IGHV gene identity is the optimal cutoff to dichotomize the prognosis of Chinese patients with chronic lymphocytic leukemia. (17th December 2019) - Shi, Ke; Sun, Qian; Qiao, Chun; Zhu, Huayuan; Wang, Li; Wu, Jiazhu; Wang, Lili; Fu, Jianxin; Young, Ken H.; Fan, Lei; Xia, Yi; Xu, Wei; et al.
Abstract: Immunoglobulin heavy chain variable region (IGHV) mutational status has been an important prognostic factor for chronic lymphocytic leukemia (CLL) for decades. Patients with unmutated IGHV (≥98% identity to the germline sequence) have inferior prognosis and tend to carry unfavorable genetic markers compared to those with mutated IGHV (<98% identity to the germline sequence). However, 98% as the cutoff for IGHV mutational status is a mathematical choice and remains controversial. We have previously reported distinct IGHV repertoire features between Chinese and western CLL populations. Here, we retrospectively studied 595 Chinese CLL patients to determine the best cutoff value for IGHV in Chinese CLL population. Using 1% as the interval for IGHV identity, we divided the studied cohort into seven subgroups from 95% to 100%. Briefer time to first treatment (TTFT) and overall survival (OS) were observed in cases with ≥98% compared to those with <98%, while the differences were obscure within subgroups ≥98% (98%‐98.99%, 99%‐99.99%, and 100%) and <98% (<94.99%, 95%‐95.99%, 96%‐96.99%, and 97%‐97.99%). Multivariate analysis confirmed the independent prognostic value of 98% being the cutoff for IGHV identity in terms of both TTFT and OS. All the prognostic factors, including del(17p13), del(11q22.3), TP53 mutation, MYD88 mutation, NOTCH1 mutation, SF3B1 mutation, CD38, ZAP‐70, Binet staging, gender, and β2‐microglobulin, were significantly different in distribution between group <98% and group ≥98%, but not among subgroups 98%‐98.99%, 99%‐99.99%, and 100%. In conclusion, 98% is the optimal cutoff of IGHV identity for the prognosis evaluation of Chinese CLL patients. Abstract : In this article, we focused on whether 98% is the best cutoff value for IGHV in Chinese patients on a 595 CLL cohort with 600 sequences in total. We found that for the whole cohort, 98% showed to be the best cutoff value for IGHV, holding prognostic value for both time to first treatment (TTFT) and overall survival (OS) in univariate analysis and being an independent prognostic factor for TTFT and OS in multivariate analysis. At the same time, all the prognostic factors were also significantly different in distribution between group <98% and group ≥98%, while the distributions among subgroups ≥98% were not significantly different. We proved that 98% IGHV is an optimal choice to predict the prognosis of CLL patients in China at present.